2009
DOI: 10.4319/lo.2009.54.1.0023
|View full text |Cite
|
Sign up to set email alerts
|

Role of phytoplankton in mercury cycling in the San Francisco Bay estuary

Abstract: To study the role of phytoplankton in mercury cycling, we measured methylmercury (MeHg) and total mercury (Hg T ) in surface waters during the spring 2003 phytoplankton bloom in San Francisco Bay. Conditions that described the peak of the bloom, the amount of sorbent, and decay of the bloom were summarized by principal component analysis (PCA). Multivariate analyses conducted with the PCA factors demonstrated that the bloom accounted for a significant (p 5 0.03) decrease in dissolved (,0.45 mm) MeHg. Dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 82 publications
(132 reference statements)
4
60
1
Order By: Relevance
“…For example, Pickhardt et al (2002) found a negative correlation between phytoplankton density and Hg concentrations in zooplankton in experimental mesocosms where nutrients were added to some treatments to stimulate algal growth. Others have found that high algal abundance in fresh (Chen and Folt 2005;Chen et al 2005) and estuarine (Luengen and Flegal 2009) waters can dilute Hg concentrations in phytoplankton (Luengen and Flegal 2009) and subsequently in fish (Chen et al 2005;Karimi et al 2007). The deep brine layer in the Great Salt Lake has very high concentrations of dissolved inorganic nutrients (Wurtsbaugh and Berry 1990).…”
Section: Depth or Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pickhardt et al (2002) found a negative correlation between phytoplankton density and Hg concentrations in zooplankton in experimental mesocosms where nutrients were added to some treatments to stimulate algal growth. Others have found that high algal abundance in fresh (Chen and Folt 2005;Chen et al 2005) and estuarine (Luengen and Flegal 2009) waters can dilute Hg concentrations in phytoplankton (Luengen and Flegal 2009) and subsequently in fish (Chen et al 2005;Karimi et al 2007). The deep brine layer in the Great Salt Lake has very high concentrations of dissolved inorganic nutrients (Wurtsbaugh and Berry 1990).…”
Section: Depth or Treatmentmentioning
confidence: 99%
“…However, the unusual nature of Great Salt Lake water, particularly the deep brine layer, complicates the interpretation. Both chloride (85 g L 21 ) and DOC (42 mg L 21 ) are very high in the mixed layer, and both of these influence Hg speciation and uptake, but not always in predictable ways (Aiken et al 2003;Pickhardt and Fisher 2007;Luengen et al 2012). Although DOC can help maintain Hg in solution, its reactivity and concentration influence biotic uptake of MeHg (Gorski et al 2006).…”
Section: Depth or Treatmentmentioning
confidence: 99%
“…Many contaminants are associated with sediment (Turner and Millward 2002;Schoellhamer and others 2007a;Luengen and Flegal 2009). Suspended sediment moving into, within, and out of estuaries provides a pathway for the transport of sedimentassociated contaminants (Turner and others 1999;Turner and Millward 2000;Bergamaschi and others 2001;Le Roux and others 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Algal bloom dilution, however, can occur for different reasons: rapid growth such that the growth rate becomes larger than the rate of Hg sequestration in phytoplankton, preferential partitioning of Hg to non-living particles (Laurier et al 2003;Schāfer et al 2006;Luengen and Flegal 2009), or limited supply of dissolved Hg species such that uptake depletes water column concentrations during early portions of a bloom (Luengen and Flegal 2009).…”
Section: Introductionmentioning
confidence: 99%